An Implicit Enumeration Algorithm for the Machine Sequencing Problem - Florian, M; Trepant, P; McMahon, G (Management science, 1971)
An implicit enumeration algorithm is developed for the machine sequencing problem. The method is based on the graph-theoretical representation of the problem. The convergence of the algorithm is demonstrated, and its efficiency is evaluated by experiments carried out with a code written for the CDC 6400 computer.